2005
DOI: 10.1080/09286580590964801
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Trauma in a Greek Population: Review of 899 Cases Resulting in Hospitalization

Abstract: Trauma is an important cause of ocular morbidity in Greece. Risk factors include young age, male gender, Albanian ethnic background, and workplace. General safety precautions and behavior modification are indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
38
3
8

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 17 publications
15
38
3
8
Order By: Relevance
“…However, for final VA, it is thought to be related with accompanying anterior and posterior segment complications like traumatic cataract, glaucoma, iridodialysis vitreus hemorrhage, macular edema, and retinal detachment, as previously reported. [1,[19][20][21][22][23][24] The results of the current study were similar to those of previous studies conducted on traumatic hyphemas in adults with respect to the frequency of complications. [1,4,14,18,22] Increase in IOP is common in traumatic hyphema patients, especially in grades 3 and 4.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, for final VA, it is thought to be related with accompanying anterior and posterior segment complications like traumatic cataract, glaucoma, iridodialysis vitreus hemorrhage, macular edema, and retinal detachment, as previously reported. [1,[19][20][21][22][23][24] The results of the current study were similar to those of previous studies conducted on traumatic hyphemas in adults with respect to the frequency of complications. [1,4,14,18,22] Increase in IOP is common in traumatic hyphema patients, especially in grades 3 and 4.…”
Section: Discussionsupporting
confidence: 89%
“…[15] Visual acuity usually decreases in patients with traumatic hyphema, especially more severally in grade 3 and 4 hyphemas. [14,[19][20][21][22] In our series, vision loss was more severe in grade 4 than grade 3 patients. The mean initial and final VA of grade 4 patients were found to be significantly lower than those of grade 3 patients.…”
Section: Discussionmentioning
confidence: 40%
See 1 more Smart Citation
“…Many epidemiological studies have reported that ocular trauma is more common among males than among females. [13][14][15][16][17][18][19] In our sample, ocular trauma was also more frequent in males, with the male:female ratios of 1.4:1 and 6:1 in the pediatric and adult groups, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The low occurrence of sports injuries in our population suggest the low priority given to sports, and this may be due to poor information about its benefits. In recent studies from developed countries, Sports related injuries have become the most common in adults [40][41][42].…”
Section: Discussionmentioning
confidence: 99%